Activating the developmental potential of the historical center to city of Baghdad (Rusafa side) - Abbas Hasan, Shatha (Journal of Planner and Development, 2023)
The types of development potential in the city vary, from the nature of city, to its society, environment, economy, and history. The city of Baghdad contains many historical development potentials out of using, and most of them towards declining, this will be the research problem, within the aim of trying to clarify how to invest one of the important historical elements in the development of the city, based on the hypothesis that the sustainable development of the city should be stand on the activation of its historical assets. The historical wall of Baghdad is located on the Rusafa side, which is a wall that has not been left except for one gate and the site of another gate from it is four gates. This wall surrounds the city of Baghdad on the side of Rusafa, it was built since the late Abbasid period, the process of demolishing its parts happened in the First World War and the loss of the Ottoman Empire and the withdrawal of its troops from Iraq. The methodology will depend on old maps showing this wall will be obtained and matched with a corrected satellites image of the city through choosing of some common features, used as ground control; points (GCP). After determining the course of the wall, the land uses of the quarry are identified for this course and suggest how they can be changed with more appropriate other land uses. The importance of choosing this element would affect the sustainable development in society. This wall has an impact on the peaceful coexistence in the city, as it protected all residents of the city without discrimination. Also, this wall laying in most valuable land in the city, so that investment in accordance with its importance economically feasible. The third aspect is that the economic investment of the cultural and historical elements is one of the cleanest investments because it preserves the environment from contaminants as opposed to other productive investments.